Social Attitude Integration and Ethnic Prejudice in Multicultural Society - Udiati, Trilaksmi; Tri Cahyono, Sunit Agus (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research to describe social attitude integration and ethnic prejudice in multicultural society. The research took place in Yogyakarta Municipality and Sleman Regency, Yogyakarta Special Province, based on consideration that the location resided by families of multicultures (heterogen), prone to interethnic conflict and brawl. Data gathering technique were interview and observation, respondents were 50 people of each location, whole was 100 respondents. Data analysis was qualitative-descriptive technique. The research showed that 79 percent respondents having social integration attitude, 21 percent having ethnic prejudice. The prevention against widening and deteriorating conflict, flaring up, social brawl are to enhance understanding, consiousness, and benefiting pluralism or various cultures as potensial resources, strength for joint progress. Social dialogue facility and communal activity by government and community need to be done. To the Directorate of Social Protection for Social Disaster Victims (PSKBS), General Directorate of Social Protection and Assurance, The Ministry of Social Affairs, need to hold a program on enhancing communal capacity (family) through socialization, education, and training of social harmony management (social integration) to prevent social conflict, set up interethnic community forum that can fill pluralism value so that families and community resilience can be realized.